2010
DOI: 10.1007/s11426-010-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalytic resonance scattering spectral analysis

Abstract: The resonance scattering spectral technique has been established using the synchronous scanning technique on spectrofluorometry. Because of its advantages of simplicity, rapidity and sensitivity, it has been widely applied to analyses of proteins, nucleic acids and inorganic ions. This paper summarizes the application of immunonanogold and aptamer modified nanogold (AptAu) catalytic resonance scattering spectral technique in combination with the work of our group, citing 53 references.antibody, aptamer, nanoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…25 Considering the surface plasmon resonances (SPR) absorption of gold nanoparticles, 26 there is a growing interest in the use of gold nanoparticles/biomolecule conjugations as the RLS probes for the analytical purpose. 27 Taking Jiang et al 28 as examples, they developed a series of resonance light scattering spectral immunoassay for protein based on the catalytic effect of antibody attached Au NPs, such as microalbumin, 29 30 complement component 3, 31 and apolipoprotein AI and B. 32 In their experiments, gold nanoparticles were coupled to antibody by physical adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…25 Considering the surface plasmon resonances (SPR) absorption of gold nanoparticles, 26 there is a growing interest in the use of gold nanoparticles/biomolecule conjugations as the RLS probes for the analytical purpose. 27 Taking Jiang et al 28 as examples, they developed a series of resonance light scattering spectral immunoassay for protein based on the catalytic effect of antibody attached Au NPs, such as microalbumin, 29 30 complement component 3, 31 and apolipoprotein AI and B. 32 In their experiments, gold nanoparticles were coupled to antibody by physical adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance of the three peaks was linearly increased with AgNPB concentration increased. The study of RRS spectra of nanoparticles in liquid phase shown that, their RRS peaks are closely related with the emission intensity of light source and the SPR absorption peaks 56 57 . The light source of model F-7000 Hitachi fluorescence spectrometer has the strongest emission wavelength at 280 nm that cause a scattering peak at 280 nm, and the emission intensity weaken as the increase of the wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…Resonance Rayleigh scattering (or resonance scattering, RS) spectral method is simple, convenient, and sensitive. It has been applied in the analysis of trace inorganic ions such as Hg(II), Cd(II), Pb(II), Mo(VI), and Cr(VI) metal ions, and organic compounds [13][14][15][16][17][18]. Based on the catalytic effect of inorganic metal ions, a catalytic RSS method has been proposed for Se [19].…”
Section: Introductionmentioning
confidence: 99%